Development of a word accentuation test for predicting cognitive performance in Portuguese-speaking populations - Gislaine Gil; Regina Miksian Magaldi; Alexandre Leopold Busse; Elyse Soares Ribeiro; Sonia Maria Dozzi Brucki; Mônica Sanches Yassuda; Wilson Jacob-Filho; Daniel Apolinario (Arquivos de Neuro-Psiquiatria)
ABSTRACT The Word Accentuation Test (WAT) has been used to predict premorbid intelligence and cognitive performance in Spanish-speaking populations. It requires participants to read a list of words without the accent marks that indicate the stressed syllable. Objective: As Portuguese pronunciation is also strongly based on accent marks, our aim was to develop a Brazilian version of the WAT. Methods: An initial pool of 60 items was constructed and a final version of 40 items (named WAT-Br) was derived by item response theory. A sample of 206 older adults underwent the WAT-Br and a standardized neuropsychological battery. Independent ratings were performed by two observers in 58 random participants. Results: The items showed moderate to high discrimination (α between 0.93 and 25.04) and spanned a wide range of difficulty (β between −2.07 and 1.40). The WAT-Br was shown to have an excellent internal consistency (Kuder-Richardson Formula 20 = 0.95) and inter-rater reliability (intraclass correlation coefficient = 0.92). It accounted for 61% of the variance in global cognitive performance. Conclusion: A version of the WAT for Portuguese-speaking populations was developed and proved to be a valuable tool for estimating cognitive performance.